2014
DOI: 10.2217/fmb.14.17
|View full text |Cite
|
Sign up to set email alerts
|

Honey Flavonoids Inhibit Candida albicans Morphogenesis by Affecting DNA Behavior and Mitochondrial Function

Abstract: HFE improved mitochondrial functionality and reduced the vacuolization, modifying the branching process associated with virulence. It is hypothesized that HFE induces changes in cell cycle progress, membrane integrity, mitochondrial function and biogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…At 24 hr, all cells formed larger clumps and had transitioned mostly to hyphae (Figure ). Another related study examined the effects of a flavonoid rich honey extract on the C. albicans phenotypic switch using similar incubation time (6 and 18 hr) used herein (Canonico et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 24 hr, all cells formed larger clumps and had transitioned mostly to hyphae (Figure ). Another related study examined the effects of a flavonoid rich honey extract on the C. albicans phenotypic switch using similar incubation time (6 and 18 hr) used herein (Canonico et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, a critical lack of knowledge remains on the ability of phenolic synergists to prevent the C. albicans hyphae phenotypes, with notable exceptions (Canonico et al, ; Kazuko, Sato, & Azuma, ; Saito, Tamura, Imai, Ishigami, & Ochiai, ). However, the referenced research does not account for responsible components or confirm whether those agents acted synergistically by constructing isobolograms or calculating the combination index (CI) (Junio et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that flavonoid part of honey decelerates the growth of fungi, affects the external morphology and membrane integrity, and inhibits some cellular processes that are involved in fungal growth and hyphal transition (Canonico et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Manuka honey has also been shown to alter the structure of P. aeruginosa; scanning and transmission electron microscopy revealed changes in cell shape and cell lysis following incubation with honey 42 . A honey flavonoid extract was also found to alter membrane integrity and branching processes associated with virulence in C. albicans 43 .…”
Section: Accepted Manuscriptmentioning
confidence: 98%